DESAIN MODEL SMARTHOME SYSTEM BERBASIS MIKROKONTROLER ATMEGA8535 - Hermawan Setiadi; Munadi Munadi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2015)
Smarthome system is the computer-based system to regulate the house that will give comfort, safety, security, and energy saving, in which it was held automatically programmed by computer. This is motivated by the limited sources of energy such as electricity or other energy, so we have to be really efficient in energy use. In this study, the smarthome system that is designed is to be used to adjust the lighting of the room, opening and closing of the gate system, switching on and off water pump system, and roof of clothes line system. In this study, we started to design a model of smarthome system by using SolidWorks software, then we create a model smarthome system using acrylic. After that, we started to programme with a CodeVisionAVR software for ATmega8535 microcontroller as brain of smarthome system. Based on the testing results that has been done, the model smarthome system is able to save electricity usage of about 28.8 percent of the ordinary house with the assumption that we set